Chess - Inspired Strategies for Effective Teaching Practices - Nur Anisnabila, Dianah; Hanisah, Kasbon; Leong Hui, Theng; Nor Safura, Nordin (UMPSA, 2025)
A bishop slips across the board, almost unnoticed. A pawn suddenly shifts the balance of the game. Within moments, a planned strategy unravels. You lean back, reconsider your next move. This is not just chess; it is a lecture hall on a Monday morning.